Crash performance of welded automotive part - Suyani, Arifin (2024)
The automotive industry aims to create vehicles with safety standards, high performance, and affordability. Crash boxes reduce impact energy during collisions and absorb kinetic energy, reducing repair costs. This study aims to alter weld arrangements to accommodate progressive folding, enhancing crush force efficiency and enhancing passenger safety. The optimum energy absorption was found through weld layout design on the single hat structure. For an ideal impact energy absorber, the initial peak force (IPF) should be minimized while the energy absorption (EA) and specific energy absorption (SEA) should be maximized. Sheet metal of AA6061-T6 with dimension 220 x 200 x 1.5 mm thickness was bend to perform single hat column and another sheet metal of AA6061-T6 was cut to dimension 200 mm x 100 mm x 1.5 mm thick. Then, two parts are spot welded together with 3 different distances from top and bottom edge which is 10 mm, 20 mm and 30 mm with 4 different spot weld number each (N=7, 8, 9 and 10). Application of the thin-walled structure under axial loading condition produce progressive collapse during crushing process which is desirable collapse mechanism. The experimental study shows that as reduced the spot weld number will reduce the IPF and reduce the distance from the top and bottom edge also decreased the IPF. Meanwhile, the highest value of EA and SEA was recorded on specimen N8D30, N9D20 and N10D10 which is 564 J and 2.26 kJ/kg. By comparing these 3 specimens shows that N8D30 optimum value due to its longest distance when IPF occur which is 4.79 mm compared to other specimen. Finaly, the optimization method using response surface method (RSM) has shown the best solution gained by the distance from top and bottom edge is 26.415 mm and spot weld number is 8.454. However, the value was rounded and found that N8D30 is the most optimum specimen through this study. Results obtain from experiment was agree with the optimize value using RSM method. As a conclusion, application optimum spot weld design layout to the structure of the crash box will increase safety and reduce vehicle damage during accident.